RESTITUTIO IN INTEGRUM: BETWEEN STATE INTERESTS VS VICTIMS IN FRAUDULENT INVESTMENT CASES (Study of Binomo Fraudulent Investment Decision) - Paulus J Karu; Febriansyah Febriansyah; Musriko Musriko (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The aim of investment is basically to gain profits in the future. However, along with the rapid development of information technology, it is increasingly having negative impacts, one of which is "fake investment", as carried out by a convict with the initials IK. What is interesting about this case is regarding the status of the convict's assets. The Tangerang District Court decided that IK's assets were confiscated by the state. The victims also felt disappointed. However, this changed at the appeal level, where the Banten High Court gave a decision that IK's assets be returned to the victim. Due to the mutual attraction between the interests of the State VS the interests of the victims, this article will discuss legal protection efforts for victims of fraudulent investments in Indonesia and the mechanisms for recovering losses both to the victims and to the national economy that arise as a result of the practice of "investment." bulging". This research uses a Legal Research Method with a statute approach and a case approach. The research results show that legal protection related to fraudulent investments still focuses on mitigation, not prevention. Apart from that, it is felt that law enforcement efforts are still less effective, especially regarding Restitutio in integrum or restoration of the original situation.